2020
DOI: 10.1142/s0217979220502951
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-indepentant multi-band unidirectional reflectionless propagation in non-Hermitian metamaterial

Abstract: We design a structure to achieve a function of polarization-independent multi-band unidirectional reflectionlessness in a non-Hermitian metamaterial system based on the Fabry-Pérot resonance. All contrast ratios of reflectance at 198 THz, 214.2 THz, and 232.65 THz are 0.99. The unidirectional reflectionless peak position remains almost unchanged with increasing polarization angles. Besides, the structure can also be used to realize the unidirectional reflectionless phenomenon in the incident angle range of 0–3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…However, in practical applications, it can be cumbersome to introduce and manipulate gain factors in metamaterial platforms and to balance them with loss factors [33,34]. Recent research shows that all-passive systems without optical gain can be engineered to demonstrate EP-related phenomena [10,[35][36][37][38][39][40]. In [12], Li et al demonstrated a passive asymmetric acoustic absorber at an EP with a compact configuration and deepsubwavelength thickness which achieves EP-induced tunable asymmetric absorption.…”
Section: Introductionmentioning
confidence: 99%
“…However, in practical applications, it can be cumbersome to introduce and manipulate gain factors in metamaterial platforms and to balance them with loss factors [33,34]. Recent research shows that all-passive systems without optical gain can be engineered to demonstrate EP-related phenomena [10,[35][36][37][38][39][40]. In [12], Li et al demonstrated a passive asymmetric acoustic absorber at an EP with a compact configuration and deepsubwavelength thickness which achieves EP-induced tunable asymmetric absorption.…”
Section: Introductionmentioning
confidence: 99%